Failure Analysis of a Total Breakdown in a Firman FPG1500ECII Generator Set Using Root Cause Identification - Toni Okviyanto; Herlin Sumarna; Tri Satya Ramadhoni; Agis Fika Wulandari; Indra Syahputra; Stevan Juliandro Aruan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Generator set failures are commonly investigated by examining individual damaged components; however, limited studies have systematically integrated failure mechanism analysis, failure propagation analysis, and Root Cause Identification (RCI) to explain the sequence of events leading to total system breakdown. This study aims to identify the failure mechanisms and root causes of a total breakdown in a Firman FPG1500ECII gasoline-powered generator set and to develop evidence-based preventive maintenance recommendations. The investigation employed a forensic engineering approach by integrating systematic visual inspection, tribological failure analysis, failure propagation analysis, Fishbone Diagram, and 5 Why Analysis. The results revealed that inadequate lubrication management was the primary initiating factor, leading to progressive piston ring wear, bearing damage, carbon deposit accumulation, valve leakage, ignition system deterioration, and ultimately complete engine failure. Failure propagation analysis demonstrated that the breakdown resulted from the interaction of multiple component failures rather than the failure of a single component. Based on the identified root causes, an evidence-based preventive maintenance schedule was developed using manufacturer recommendations and previous maintenance studies. The principal contribution of this study is the development of an integrated engineering failure analysis framework that systematically links failure mechanisms, failure propagation, and Root Cause Identification to support maintenance decision-making and improve the reliability of gasoline-powered generator sets operating under similar conditions. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production